Noventa años de Teología moral en la revista Estudios Eclesiásticos (1922-2012) - Julio L. Martínez, S. J. (Estudios eclesiásticos, 2012)
The present article does a tour for the presence of topics of Moral Theology throughout ninety years of existence of the review Estudios Eclesiásticos. The authors realize of the problems that have been more present and the professors of the Institutions of the Society of Jesus in Spain that have contributed to moral reflection, with a particular attention to those that more collaborations have realized throughout this time as the P. Zalba. Likewise they offer some reasons that explain the significant, but to a certain extent shy, of the Moral Theology in the review, if we compare it with other areas of the systematic theological one. In the final part there is included a relation of articles classified by thematic blocks that ensues from great usefulness to know the whole production of the magazine in the diverse disciplines that after the Council Vatican II shape the corpus of the Moral Theology.